Diagnosis of a Rare Tumor “Solitary Plasmacytoma of Bone” - Islam, Md Jubaidul; Sultana, Tasnia; Mahmuda, Farzana; Ahmed, Jamal Uddin (Journal of Medicine, 2022)
Solitary plasmacytoma of bone (SPB, also called osseous plasmacytoma) is a localized tumor in the bone comprised of a single clone of plasma cells in the absence of other features of MM (Multiple Myeloma). Most patients present with skeletal pain or a pathologic fracture of the affected bone. Patients with vertebral involvement may have severe back pain or neurologic compromise (e.g. cord compression). J MEDICINE 2022; 23: 173-175